RhoA GTPase-Induced Ocular Hypertension in a Rodent Model Is Associated with Increased Fibrogenic Activity in the Trabecular Meshwork - Pattabiraman, Padmanabhan P. (Am J Pathol, 2015)
Ocular hypertension arising from increased resistance to aqueous humor (AH) outflow through the trabecular meshwork is a primary risk factor for open-angle glaucoma, a leading cause of blindness. Ongoing efforts have found little about the molecular and cellular bases of increased resistance to AH outflow through the trabecular meshwork in ocular hypertension patients. To test the hypothesis that dysregulated Rho GTPase signaling and a resulting fibrotic activity within the trabecular meshwork may result in ocular hypertension, we investigated the effects of expressing a constitutively active RhoA GTPase (RhoAV14) in the AH outflow pathway in Sprague-Dawley rats by using lentiviral vector-based gene delivery. Rats expressing RhoAV14 in the iridocorneal angle exhibited a significantly elevated intraocular pressure. Elevated intraocular pressure in the RhoAV14-expressing rats was associated with fibrotic trabecular meshwork and increased levels of F-actin, phosphorylated myosin light chain, α-smooth muscle actin, collagen-1A, and total collagen in the trabecular AH outflow pathway. Most of these changes were ameliorated by topical application of Rho kinase inhibitor. Human autopsy eyes from patients with glaucoma exhibited significant increases in levels of collagen-1A and total collagen in the trabecular AH outflow pathway. Collectively, these observations indicate that increased fibrogenic activity because of dysregulated RhoA GTPase activity in the trabecular AH outflow pathway increases intraocular pressure in a Rho kinase-dependent manner.